Analyzing Basketball Techniques for Performance Enhancement: A Comprehensive Literature Review - Ihsani, Sri Indah; S, Adi; Aljriad, Hilmi; Redy Utama, Made Bang (Jurnal Kepelatihan Olahraga, 2026)
Background: Enhancing basketball player performance requires a clear understanding of effective movement techniques. This study aims to synthesize and analyze key biomechanical techniques that influence performance, based on a systematic review of recent research. Methods: Following PRISMA guidelines for systematic reviews and meta-analyses, a comprehensive literature search was conducted using the Scopus database. The search targeted studies published between January 2020 and December 2024 using the keywords “basketball” and “biomechanics.” After three stages of screening based on predefined inclusion and eligibility criteria, 13 articles were selected from an initial pool of 231 for in-depth analysis. Results: The selected studies provided comprehensive insights into the biomechanical variables affecting basketball performance. Participants included both male and female athletes, with some studies emphasizing external conditions such as fatigue as injury risk factors. Key biomechanical factors identified include knee inversion and rotational moments, ground reaction forces, ankle stability, lower-limb characteristics, midsole hardness, joint loading during landing, core activation and stability, joint angles, knee flexion velocity, dynamic balance, directional changes, and shoulder positioning. Conclusion: Player performance in basketball is influenced by multiple biomechanical elements, including movement efficiency, joint stability, muscular strength, and technical execution. External factors such as fatigue and footwear characteristics also play a significant role in injury prevention and performance optimization. These findings support the need for targeted, biomechanically informed training interventions in basketball.